2002
DOI: 10.1001/archpsyc.59.2.173
|View full text |Cite
|
Sign up to set email alerts
|

Prefrontal Cortical Volume in Childhood-Onset Major Depression

Abstract: These results provide new evidence of prefrontal cortical alterations in pediatric MDD that may differ in familial and nonfamilial subtypes of MDD. Our findings must be considered preliminary, however, in view of the small sample size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
1
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 119 publications
(57 citation statements)
references
References 79 publications
(88 reference statements)
1
53
1
2
Order By: Relevance
“…[13,14] This result explains some of the hereditary aspects of depression, thereby indicating the association of the neuroimaging findings with the risk factors on depression. [15,16] In a study on functional neuroimaging, there is a remarkable mood-down-regulation effect due to the increased task in the normal group with a family history of depression than in the normal group without a family history of depression. Furthermore, the activation of the amygdala significantly increased in the normal group with a family history of depression as compared to the other group.…”
Section: Prediction Of the Risk Factors On Depressionmentioning
confidence: 99%
“…[13,14] This result explains some of the hereditary aspects of depression, thereby indicating the association of the neuroimaging findings with the risk factors on depression. [15,16] In a study on functional neuroimaging, there is a remarkable mood-down-regulation effect due to the increased task in the normal group with a family history of depression than in the normal group without a family history of depression. Furthermore, the activation of the amygdala significantly increased in the normal group with a family history of depression as compared to the other group.…”
Section: Prediction Of the Risk Factors On Depressionmentioning
confidence: 99%
“…On the University of Pittsburgh MR scanner a three dimensional SPGR acquisition in the steady state pulse sequence was utilized to obtain 1.5 mm coronal images (TE = 20 msec, TR = 40 msec, acquisition matrix = 256 x 192, FOV = 20 cm, flip angle = 10°). Image acquisition has been described in detail in our previous reports (Gilbert et al, 2000, MacMaster and Kusumakar, 2004a, MacMaster and Kusumakar, 2004b, MacMaster et al, 2006, Nolan et al, 2002, Rosenberg et al, 1997, Szeszko et al, 2004a, Szeszko et al, 2004b. All MRI scans were reviewed to rule out any clinically significant abnormalities.…”
Section: Image Acquisition and Analysismentioning
confidence: 99%
“…Some morphometric studies reported white matter deficits in the frontolimbic (Steingard et al 2002) and temporal (Li et al 2007) regions. Region of interest (ROI) analyses displayed gray matter deficits in the hippocampus (MacMaster and Kusumaker 2004;Caetano et al 2007;Rao et al 2010) and prefrontal cortex (PFC; Nolan et al 2002) in depressed youngsters. Similarly, gray matter deficits in the hippocampus (Bremner et al 2000;Ballmaier et al 2004;Campbell et al 2004;Vasic et al 2008), orbitofrontal cortex (OFC; Lacerda et al 2003;Vasic et al 2008), dorsolateral prefrontal cortex (DLPFC; Vasic et al 2008), and cingulate gyrus (Vasic et al 2008;Zhou et al 2010) have been observed in adult subjects with MDD.…”
Section: Introductionmentioning
confidence: 99%